Sosialisasi Cara Menciptakan Peluang Usaha dan Rebranding pada UMKM Kecamatan Kalisat - Ibna Kamilia Fiel Afroh; Achmad Hasan Hafidzi; Nesca Aurelia; Della Vera Andiny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
A village-owned enterprise is a local business institution managed by the village government and has a legal entity. The impact of Covid-19, which appeared some time ago, has destabilized the economy of the village. As a result, almost all business units will be unable to operate. Insufficient awareness of business opportunities using social media, etc. Based on the priority challenges faced by our partners, the first solution offered is a socialization program that creates business opportunities and rebrands the company to make it more attractive. Based on observations of customers from different industries in Kalisat Village. Problems encountered in village businesses include the lack of development and exploitation of various existing business opportunities, the need to support existing human resources to improve the business, and marketing to make it attractive and innovative. There is such a thing as rebranding as an aid. Observation/Interview Socialization/Discussion The potential of the environment is introduced in an easy-to-understand manner using videos, and examples of business opportunities are introduced. We provide knowledge and understanding reading opportunities training for small businesses and creative industries on how to make the most of information technology as part of their business development to compete globally. Companies that need further development can proceed to the rebranding process. Based on the issues faced by partners, a socialization program is implemented as a learning proposition for his MSME actors to show them how to seize the opportunities around them and improve the quality of their products or brand. The socialization and counseling process can be carried out over several sessions to allow people to consistently develop their potential and environment.